Cassini composite infrared spectrometer: correcting an offset error and refining the pointing parameters for the midinfrared detectors - Pearl, JC; Nixon, CA; Jennings, DE; Aslam, S; Calcutt, S; Kaelberer, MS; Gorius, N; Achterberg, RK; Bjoraker, GL; Romani, PN; Flasar, M (Optica, 2023)
Based on preflight laboratory testing, an unexpectedly large positional offset between the two midinfrared (mid-IR) detector arrays in the Cassini composite infrared spectrometer (CIRS) instrument has been noted in the literature. A much smaller offset was measured in-flight. We investigate this discrepancy by estimating several spatial relationships among the detectors and comparing these results with three independent data sets. This enables us to infer the probable cause of this offset and to derive a new reduced value. We comment on the effect that this change could have on previously published results involving CIRS data. We also present a graphical display of the arrays projected on the sky as CIRS would see it.